B Cell Receptor Immunogenetics in B Cell Lymphomas: Immunoglobulin Genes as Key to Ontogeny and Clinical Decision Making - Gemenetzi, Katerina; Agathangelidis, Andreas; Zaragoza-Infante, Laura; Sofou, Electra; Papaioannou, Maria; Chatzidimitriou, Anastasia; Stamatopoulos, Kostas (Frontiers in Oncology, 2020)
The clonotypic B cell receptor immunoglobulin (BcR IG) plays a seminal role in B cell lymphoma development and evolution. From a clinical perspective, this view is supported by the remarkable therapeutic efficacy of BcR signaling inhibitors, even among heavily pre-treated, relapsed/refractory patients. This clinical development complements immunogenetic evidence for antigen drive in the natural history of these tumors. Indeed, BcR IG gene repertoire biases have been documented in different B cell lymphoma subtypes, alluding to selection of B cell progenitors that express particular BcR IG. Moreover, distinct entities display imprints of somatic hypermutation (SHM) within the clonotypic BcR IG gene following patterns that strengthen the argument for antigen selection. Of note, at least in certain B cell lymphomas, the BcR IG genes are intraclonally diversified, likely in a context of ongoing interactions with antigen(s). Moreover, BcR IG gene repertoire profiling suggests that unique immune pathways lead to distinct B cell lymphomas through targeting cells at different stages in the B cell differentiation trajectory (e.g. germinal center B cells in follicular lymphoma, FL). Regarding the implicated antigens, although their precise nature remains to be fully elucidated, immunogenetic analysis has offered important hints by revealing similarities between the BcR IG of particular lymphomas and B cell clones with known antigenic specificity: this has paved the way to functional studies that identified relevant antigenic determinants of classes of structurally similar epitopes. Finally, in certain tumors, most notably chronic lymphocytic leukemia (CLL), immunogenetic analysis has also proven instrumental in accurate patient risk stratification since cases with differing BcR IG gene sequence features follow distinct disease courses and respond differently to particular treatment modalities. Overall, delving into the BcR IG gene sequences emerges as key to understanding B cell lymphoma pathophysiology, refining prognostication and assisting in making educated treatment choices.